On the basis of the direct product of paths and wheels - A. A. Al-Rhayyel (International Journal of Mathematics and Mathematical Sciences)
The basis number, b(G), of a graph G is defined to be the least integer k such that G has a k-fold basis for its cycle space. In this paper we determine the basis number of the direct product of paths and wheels. It is proved that P2∧Wn,is planar, and b(Pm∧Wn)=3, for all m≥3 and n≥4.